Relaparotomy in Obstetrics and Gynaecology Department of Faridpur Medical College Hospital - Experience in One Year - Alam, Irin Parveen; Mahbuba, Dr.; Das, Shila Rani (Faridpur Medical College Journal, 2013)
After abdominal surgery some patient's needs relaparotomy for complications developed postoperatively. Aim of this study was to determine the risk factors causing re-laparotomy, the indications, management and outcomes of relaparotomy admitting in Obstetrics and Gynaecology department in Faridpur Medical College Hospital, a tertiary referral hospital where all complicated patients are referred for management from surrounding districts hospital. It was a cross sectional study done during the period of January 2011 to December 2011, All the cases among which relaparotomy were done after primary surgery were recorded using a protocol prepared for the study. Data was analyzed. Total 6304 patients were admitted in emergency way in Obstetrics and Gynaecology department of Faridpur Medical College Hospital. Among them 1864 patients undergone emergency operations, here 15 patients needed re-laparotomy. The incidence of re-laparotomy was 0.80%. Indications of relaparotomy included internal hemorrhage, postpartum hemorrhage (PPH), retained foreign body, incorrect diagnosis at first laparotomy, intraabdominal collection of pus and urine, Rectus sheath haematoma and burst abdomen. Often more than one procedure was needed to manage the cases. Re-laparotomy causes much morbidity & mortality with increase in hospital stay and cost. Careful selection of cases for primary operation, expertise of the surgeon, good surgical technique and careful postoperative follow-up can reduce the need for re-laparotomy. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13503 Faridpur Med. Coll. J. 2012;7(2):75-78